Nota sobre la incidencia del embalse de Itaipú en la ictiofauna paranense de los tramos inferiores - Bonetto, Argentino A.; Wais, Irene R. (Ecosur, 2023)
The hoge Itaipú dam recently estabiished in Brazil Crossing the Paraná River, defines at present, the real Southern lhnit of the Superior Paraná. The printitive one, the Guayrá falls, are now coveréd by the resúltiug mán-ntade lake. The biotic composition of the Superior Paraná is rather poor and differeat from the other streches, párticulaily in the integration of theichthyofauna, havkig an important number of endemic species, as well as several introduced fishes, intra and extra Neotropical area. At it is evident, in thejaew condition these fishes may traverse the damby the turbines and disregarding the lpsse, they would spread out in the remaining treitdsof the river, particularly in the reach of the highest temperaturas. It is difficult to estimate the ecológical impact of this phenomenon, particularly in fishery pioductivity of the water. The authors consider that it is very interestingand important to study the nature and real impact of Itaipú in this direction, andoveiíi^is baseline, to promote multinational investigations in order to avoid important lateral síde effects specially on fisheries.